A Novel Anti-Cancer Therapy: CRISPR/Cas9 Gene Editing - Chen, Xin-Zhu; Guo, Rong; Zhao, Cong; Xu, Jing; Song, Hang; Yu, Hua; Pilarsky, Christian; Nainu, Firzan; Li, Jing-Quan; Zhou, Xin-Ke; Zhang, Jian-Ye (Frontiers in Pharmacology, 2022)
Canner becomes one of the main causes of human deaths in the world due to the high incidence and mortality and produces serious economic burdens. With more and more attention is paid on canner, its therapies are getting more of a concern. Previous research has shown that the occurrence, progression, and treatment prognosis of malignant tumors are closely related to genetic and gene mutation. CRISPR/Cas9 has emerged as a powerful method for making changing to the genome, which has applied in various cell lines extensively. CRISPR-Cas9-mediated genome editing technology brings great promise for inhibiting the migration, invasion and even treatment of tumor. However, potential off-target effect limits its clinical application. The article reviews the molecular mechanisms of CRISPR/Cas9 and discusses the research related to cancer clinical trials.